KORELASI ANTARA LAMA MENDERITA DIABETES MELITUS DENGAN NILAI AMBANG PENDENGARAN - , Heri Puryanto, dr.Kartono Sudarman, Sp.THT-KL(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetes mellitus (DM) is a group of metabolic diseases which have a characteristic of hyperglycemia that occurs because of abnormalities in insulin secretion, insulin action, or both. One of the complications of chronic diabetes on the nerve is diabetic neuropathy, which may result in impaired sensitivity or changes in threshold of hearing. A cross-sectional designed study was conducted to the patients suffering from DM to determine the correlation between length of suffering DM and hearing threshold in Dr. Sardjito Hospital Yogyakarta. Examination were conducted on the research subjects, to assess bone conduction hearing threshold at a frequency of 2000Hz, 4000Hz, and 6000Hz using audiometer. The length of chronic DM were specified by the author to be 1 year, 2 years, and 3 years continuously, but we did not analize the levels of HbA1c due to the lack of complete data. Spearman correlation test was applied to analyse the data. The results observed at all frequencies obtained values of p >0.05, but for patients who suffer from diabetes more than 9 years obtained values of p<0.05 at a frequency of 4000Hz left, 6000Hz right and left Based on these results, it can be concluded that there is a weak positive correlation between length of suffering from diabetes mellitus with hearing thresholds, but for people with more than 9 years there is a strong positive correlation at high frequency.